Molecular Structural Elucidation of Coloumn Secondary Fraction in Malvaviscus penduliflorus (Malvaceae) - Asadulla, Syed (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
Malvaviscus penduliflorus (Malvaceae) is a popular erect under shrubs. It is garden ornamental widely grown across tropical and subtropical regions. The plant widely grown as both garden ornamentals and medicinal plants with varied ethnomedical uses, mostly for wounds, fever, hypertension, sore throat, bronchitis, gastritis, and liver and gall bladder problems. The pharmacognostic studies such as moisture content, ash values, extractive values, histology, and powder analysis were carried out. Successive solvent extraction and phytochemical screening were carried out. The extracts showed the presence of alkaloids, glycosides, phenols, steroids, terpenoids, carbohydrates, and saponins. The fraction was extracted from leaves and purified by column chromatography. The phytochemical studies gave conformation of the above said results. Molecular Formula: C20H18O10, Formula Weight: 418.354, Composition: C(57.42%) H(4.34%) O(38.24%) 16-(25,27-dihydroxyphenyl)-8-hydroxy-11,12-dihydro-15H-7-benzopyran-10-one)-5-(hydroxymethyl)-3-hydrofuran-2,4,6-triol.